THE USE OF ICT IN TEACHING PROCESS BY PUBLIC JUNIOR HIGH SCHOOL ENGLISH TEACHERS IN TAMPAN SUB-DISTRICT PEKANBARU - Pratiwi, Andini; Hadriana, Hadriana; Daud, Afrianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to investigate to what extent the English teachers of public junior high schools in Tampan Sub-District Pekanbaru have used ICT and identify the barriers they face in the use of ICT in their teaching process. The researchers selected 16 English teachers as the sample using total sampling method. This research applied a mixed-method, combining quantitative and qualitative methods of data collection. The quantitative data were collected by distributing a set of questionnaires. The indicators of the questionnaire used are Perceived Usefulness and Perceived Ease of Use. The qualitative were acquired through semi-structured interviews. The combination of the two types of data was chosen to get more information to support the data. The findings show that teachers have integrated ICT in their teaching process was in good category level. This can be seen from the result of the study in which the overall mean score calculated was 3.67. Still, teachers faced some problems in its integration. In general, the problems related to lack of ICT facilities and electricity issues.Key Words: ICT, English Teachers’ perception, teaching and learning process.